Aquascape Techniques as an Alternative Livelihood During the COVID-19 Pandemic in Percut Sei Tuan Village - Hasibuan, Julia Syahriani; Rizky Febriansyah Siregar; Khairunnisa; Astrid Fauzia Dewinta; Vindy Rilani Manurung (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Percut Village is one of the villages located on the East Coast of North Sumatra which is directly opposite the waters of the Malacca Strait so that the main livelihood of the villagers is as fishermen. During pandemic, the government has implemented a Large Scale Social Restriction policy which has an impact on the social status of the community, such as limited fishing activities which have resulted in a decrease in the selling price of caught fish. In addition, the silting of sedimentation in 2020 resulted in the tides and coastline becoming unclear so that fishermen could not go to sea optimally. Based on these considerations, knowledge dissemination and training on techniques for creating aquascapes have been carried out for groups of young fishermen in July – September 2021 in Percut Village, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra Province, North Sumatra Province. The results of this activity have a positive impact on the community to increase creativity and enrich soft skills by applying the knowledge gained to start becoming an entrepreneur as an alternative livelihood for fishermen youth groups so that they are able to compete in the midst of society and can create jobs.